The Prince - Samhita Arni (Juggernaut Books, 2019)
The famous dancer Madhavi is at the court of the Chera King for a grand performance. The King's first son Shenguttuvan, the crown prince of the Cheras, is getting ready for his engagement to a Velir princess. There is celebration in the air. But when an astrologer predicts that the second son Uthiyan is destined to be greater than his elder brother, the Chera court erupts in chaos. The courtiers begin to play the brothers against each other. Life becomes dangerous for Uthiyan and the prince is forced to flee his home in the garb of a monk. In a perilous journey beset by assassins and conspirators, he is joined by others who seek refuge at the just court of the Pandya King. But darkness is descending on the ancient city of Madurai. Warriors from the west, the single-minded and ruthless Kalabhras, have set out to conquer the prosperous Pandya capital and change the face of Tamilaham. Tormented rage and lust, beset by betrayal and terror, Uthiyan is forced to choose a side in a conflict that is certain to end in bloody violence.